The unspeakable, gender and sexuality in medieval literature, 1000-1400 - Blud, Victoria (Gender in the Middle Ages, 2017)
An investigation of the motif of the unspeakable as manifested in a wide range of medieval texts, from the Exeter Book to Chaucer.